Sistem Pendukung Keputusan Pemilihan Lokasi Perumahan Terbaik Menggunakan Metode TOPSIS di Daerah Jalan Baru - Yogi Syahputra; Rizky Sapandi Panggabean; Lela Budiarti (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2026)
The selection of an optimal housing location is a complex decision-making process involving multiple conflicting criteria, such as accessibility, environmental conditions, land price, and proximity to public facilities. This study develops a Decision Support System (DSS) for selecting the best housing location in the Jalan Baru area using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The TOPSIS method is chosen for its ability to rank alternatives based on their geometric distance to both positive and negative ideal solutions. Several criteria were considered, including land price, distance to the city center, road access, availability of utilities (water, electricity), and proximity to schools, markets, and health facilities. Data were collected through field surveys and spatial analysis. The results show that the TOPSIS method effectively identifies the most suitable housing location by providing a clear preference order among alternatives. The proposed DSS offers a transparent, systematic, and objective tool for property developers and local governments to support housing site selection decisions. This study contributes to the application of multi-criteria decision-making in urban planning and real estate development